PUNJERING NGAURIP: Understanding the Yogyakarta Palace on the Philosophical Axis of the Yogyakarta Palace in the Perspective of Cultural Philosophy - Permadi, Danur Putut; Teguh; Kholis, Nur (Asketik: Jurnal Agama dan Perubahan Sosial, 2024)
This research is motivated by the efforts of the Yogyakarta regional government to submit the Yogyakarta Palace's Philosophical Axis as a cultural heritage to UNESCO. This axis is a road that stretches from the Krapyak Stage, the Yogyakarta Palace, and the Yogyakarta Monument. This axis is the implementation of one of the Javanese philosophies, Sangkan Paraning Dumadi. This philosophy explains that humans must be able to understand how they can be born in this world and what their goal is born. This study aims to analyze the meaning of the Yogyakarta Palace in the philosophical axis and analyze the position of the Yogyakarta Palace using the perspective of cultural philosophy. The data obtained in this study came from in-depth interviews and documentation. By using a phenomenological approach, it is found that the Yogyakarta Palace is the center of the Philosophical Axis because it symbolizes harmony and eternity between the people, nature and the king. Besides, in the Mitis stage, the palace is interpreted as a sacred complex where various traditional ceremonies take place. And at the functional stage, the palace is not only interpreted as part of the philosophical axis. And at the functional stage, the palace is not only interpreted as part of the philosophical axis. But also interpreted as the center of tourist destinations in the city of Yogyakarta. From these findings it can be concluded that there has been a shift in the meaning of the Yogyakarta Palace as the center of the philosophical axis into one of the tourist attractions that are economically valuable.